2020
DOI: 10.1021/acsinfecdis.9b00354
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Lead Compounds Targeting the Selenoprotein Thioredoxin Glutathione Reductase for Treatment of Schistosomiasis

Abstract: Schistosomiasis is a widespread human parasitic disease currently affecting over 200 million people. Chemotherapy for schistosomiasis relies exclusively on praziquantel. Although significant advances have been made in recent years to reduce the incidence and intensity of schistosome infections, these gains will be at risk should drug-resistant parasites evolve. Thioredoxin glutathione reductase (TGR) is a selenoprotein of the parasite essential for the survival of schistosomes in the mammalian host. Several hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(30 citation statements)
references
References 55 publications
0
29
0
Order By: Relevance
“…Taking these concerns into consideration and given the modern resources of drug development, synthesis of PZQ derivatives [8], discovery of alternative lead compounds [9,10], natural products [11,12] and repurposing of existing drugs [13,14] are effective approaches for the introduction of new antischistosomal agents. Recently, we demonstrated that miltefosine (MFS), a membrane active alkylphosphocholine, is a promising repurposing candidate against schistosomiasis [13,15].…”
Section: Introductionmentioning
confidence: 99%
“…Taking these concerns into consideration and given the modern resources of drug development, synthesis of PZQ derivatives [8], discovery of alternative lead compounds [9,10], natural products [11,12] and repurposing of existing drugs [13,14] are effective approaches for the introduction of new antischistosomal agents. Recently, we demonstrated that miltefosine (MFS), a membrane active alkylphosphocholine, is a promising repurposing candidate against schistosomiasis [13,15].…”
Section: Introductionmentioning
confidence: 99%
“…These inhibitors may be especially reactive with TrxR1 due to its crucial and highly nucleophilic selenocysteine (Sec) residue in the active site of the enzyme [ 15 , 23 ]. Stattic was furthermore recently found to target the TrxR1 orthologue of Schistosoma mansoni , again likely by binding directly to its Sec residue [ 24 ]. In addition, a potent inhibitor of TrxR1, Auranofin, which is clinically approved for treatment of rheumatoid arthritis and currently in trials for anticancer treatment, was also shown to potently inhibit Interleukin-6 dependent JAK1/STAT3 phosphorylation [ 25 ].…”
Section: Introductionmentioning
confidence: 99%
“…A recent work selected the most active chemotypes from HTS plus analogues and re-tested against the enzyme. Ninety-seven had SmTGR inhibitory activity confirmed, and five of them killed S. japonicum, S. haematobium and S. mansoni (with LD 50 ≤ 10 µM) adult worms, and all other development stages of S. mansoni (138). SmTGR has also been recently explored under the fragmentbased drug discovery paradigm, as it will be discussed further ahead in this review.…”
Section: Target-based Screeningmentioning
confidence: 99%